THE USE OF BPJS DIGITALIZATION PROGRAMS TO IMPROVE SERVICE QUALITY IN FACING THE INDUSTRIAL REVOLUTION 4.0 ERA - Clinton Antony; Ermi Girsang; Sri Lestari Ramadhani Nasution (Pena Cendekia Insani, 2025)
The Industrial Revolution 4.0 era demands digital transformation in various sectors, including the health sector. One form of innovation in health services is the digitalization of the BPJS Kesehatan program, which aims to improve the efficiency and quality of services in health facilities. This study aims to assess the effectiveness of the use of BPJS program digitalization to improve the quality of services in facing the industrial revolution 4.0 era at Royal Prima Medan Hospital, as well as to identify obstacles faced in its implementation. The research method used is a qualitative study, where data was obtained through interviews with the hospital director, the head of the BPJS primary benefit guarantee division, and six patients using BPJS services. The results of this paper indicate that the use of BPJS digitalization at Royal Prima Medan Hospital has been running in accordance with the Standard Operating Procedure (SOP) and has had a positive impact on the acceleration of the administrative process, queue efficiency, and patient data integration. However, there are still several obstacles, such as technical disruptions in the system, limited patient understanding of technology, and instability of the internet network, which can affect the effectiveness of services. To overcome these obstacles, the hospital has made various efforts, such as providing a help desk, improving digital infrastructure, and education for patients and medical personnel. Overall, the digitalization of the BPJS Kesehatan program at RSU Royal Prima Medan has proven effective in improving the quality of service, although further system optimization and innovation are still needed so that the implementation of this digitalization can run optimally in accordance with the demands of the Industrial Revolution 4.0.